2019
DOI: 10.1055/s-0039-1694772
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Testing for Thrombophilia-Related Genes: Observations of Testing Patterns for Factor V Leiden (G1691A) and Prothrombin Gene “Mutation” (G20210A)

Abstract: Thrombophilia is a generic term that defines an increased propensity toward thrombosis and associated morbidity. Factor V Leiden (FVL; G1691A) and the prothrombin gene mutation (PGM; G20210A) comprise the most common genetic associations with thrombosis, and thus comprise the most commonly requested genetic thrombophilia investigations. This report describes an audit of local test findings that suggests growing futility in testing for FVL and PGM. Test requests for FVL and PGM were assessed for a recent period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 59 publications
(64 reference statements)
0
21
0
1
Order By: Relevance
“…6 However, most experts and evidence-based guidelines argue against such measurements due to a lack of benefits. 2 Furthermore, the risk of thrombosis increased significantly in prothrombin G20210A and FV G1691A mutation carriers using combined hormonal contraceptives (CHCs). 7,8 Altogether, FV G1691A and FII G20210A testing might identify individuals at risk of recurrent thrombotic episodes for targeted further intervention, but other data do not support this approach.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…6 However, most experts and evidence-based guidelines argue against such measurements due to a lack of benefits. 2 Furthermore, the risk of thrombosis increased significantly in prothrombin G20210A and FV G1691A mutation carriers using combined hormonal contraceptives (CHCs). 7,8 Altogether, FV G1691A and FII G20210A testing might identify individuals at risk of recurrent thrombotic episodes for targeted further intervention, but other data do not support this approach.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Altogether, FV G1691A and FII G20210A testing might identify individuals at risk of recurrent thrombotic episodes for targeted further intervention, but other data do not support this approach. 2 Individual II-1 had recurrent in vitro fertilization failures on the 12th gestational week due to the occurrence of DVT in the fetus. Genetic testing revealed that she is a heterozygous carrier for both MTHFR C677T and FV G1691A mutations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a noteworthy article, Crispin and Koo 7 discuss important practical and institutional ethical considerations surrounding the provision of a molecular diagnosis and describe how molecular tests are currently being employed in clinical practice to inform diagnostic, clinical decision making, and treatment approaches for individuals across disorders of hemophilia, rare bleeding disorders, platelet disorders, and thrombotic disorders. This review is followed by a provocative report by Favaloro 18 who assesses the testing patterns of two common low-risk thrombophilia inherited genetic variants, factor V Leiden (G1691A) and the prothrombin gene G20210A mutation as performed at a large tertiary institution. The data presented demonstrate the accessibility of these genetic tests to referring physicians in everyday clinical practice.…”
mentioning
confidence: 99%